TINGKAT PARTISIPASI ANGGOTA KELOMPOK WANITA TANI DALAM PROGRAM MODEL KAWASAN RUMAH PANGAN LESTARI (M-KRPL) DI DESA TUALANG KECAMATAN TUALANG KABUPATEN SIAK - Risky Nurjannah; Roza Yulida; Eri Sayamar (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2015)
The purpose of this study is to identify the level of participation and participation problems that faced KWT members in M-KRPL program in Tualang village. The survey method was used in the study, while Simple Random Sampling was also used as the sampling technique. The number of respondents were 28 samples. The samples was taken of the KWT Cendana Wangi members who followed M-KRPL program in Tualang village. Analysis level of participation and problem KWT members that faced in the participation of this study was descriptive method. In measured level of participation can be through participation in planning, implementation, use of the results and evaluation. The level of participation data members used questionnaire, Scale of Liker’s Summated Rating (LSR) was used. The result showed the level of participation KWT members was categorized as ”high level” with the score 3,88. The level of participation was categorized high be supported the based high score of participation members such as planning, implementation, use of the results and evaluation. M-KRPL program in Tualang Village consist of participation KWT members problems in the development program. The participation problems faced by members namely, problems of production facilities, water availability, disclosure issues, the problems participation of member KWT in the planning and implementation program. Keywords: Participation, Sustainable Food Houses Region, Sustainable Food Houses, Women Farming Group.